2017
DOI: 10.17265/2161-6264/2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnetic Water Irrigation on the Growth, N Uptake and Antioxidant Enzyme Activities of Cotton Seedlings

Abstract: A hydroponic experiment was carried out to investigate the effects of magnetic water irrigation on the growth, nutritional status and antioxidant enzyme activity of cotton seedlings. Four levels of magnetic-treated water irrigation (0, 100, 300 and 500 mT) and three levels of salt stress (0, 100 and 200 mM NaCl) were applied. Salt stress adversely affected the dry weight, nutrient uptake and antioxidant enzyme activities of cotton seedlings. Magnetic-treated water irrigation significantly increased cotton seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Rice has also exhibited improvements in response to magnetized‐ionized water irrigation, with increased SPAD value, dry matter accumulation, effective panicle number, seed setting rate, and yield 25 . Other investigations have revealed the significant effects of magnetized‐ionized water irrigation on pak choi, eggplants, and cotton 45,60‐63 . Olant height, stem diameter, leaf number, and crop yield were notably augmented due to this treatment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Rice has also exhibited improvements in response to magnetized‐ionized water irrigation, with increased SPAD value, dry matter accumulation, effective panicle number, seed setting rate, and yield 25 . Other investigations have revealed the significant effects of magnetized‐ionized water irrigation on pak choi, eggplants, and cotton 45,60‐63 . Olant height, stem diameter, leaf number, and crop yield were notably augmented due to this treatment.…”
Section: Discussionmentioning
confidence: 93%
“…25 Other investigations have revealed the significant effects of magnetized-ionized water irrigation on pak choi, eggplants, and cotton. 45,[60][61][62][63] Olant height, stem diameter, leaf number, and crop yield were notably augmented due to this treatment. This study has revealed that magnetized-ionized water irrigation enhanced key parameters including H, LAI, DM, and SPAD during the cotton seedling period.…”
Section: Effects Of Magnetized-ionized Water Irrigation On Crop Growthmentioning
confidence: 95%
“…This could be attributed to the fact that the H 2 O 2 in the magnetoelectric water promoted the establishment of the spinach antioxidant defense mechanism, alleviated the damage to the spinach photosynthetic apparatus caused by active oxygen accumulation induced by water stress, and thus improved the ability of the spinach to assimilate photosynthetic carbon. Experiments have demonstrated that magnetized water could enhance antioxidase activities in kidney beans (Phaseolus vulgaris) and lettuce (Lactuca sativa) to enhance stress resistance [59,60].…”
Section: Effects Of Soil Moisture Content and Magnetoelectric Water O...mentioning
confidence: 99%